Language Selection to Attract Customers’ Attention: Verbal Branding and Representation of Specific Ethnicity - Junaidi, Junaidi (REiLA : Journal of Research and Innovation in Language, 2022)
Words can motivate individuals to take action. In culinary sector, distinct ethnic verbal branding is one of the techniques to identify a restaurant brand. Specific phrases or words are selected to establish a powerful brand. This study aims to analyze the language selection for verbal branding and ethnicity representation in restaurants that use ethnic brands in Pekanbaru, one of the metropolis cities with the largest economic activities in Sumatera Island. Six restaurants were selected for their popular atmosphere, service, and cuisines authenticity specific to ethnic brand. This qualitative research was conducted from the perspective of cultural studies using an ethnolinguistic approach to collect data from three-month observations and interviews with the owners of purposively-selected restaurant to help understand the phenomenon. The results indicated that, lexically, the names of the restaurants contained ethnic words directly associated with certain ethnicities and are chosen to create a memorable brand. The analysis of associative meaning reveals that the restaurant brand represents an ethnicity with its uniqueness to produce strong branding which attracts customers. The combined lexical and associative meaning shows that restaurant branding represents not only the restaurant owners’ place of origin or ethnicity but also the authentic menus that define their culinary business. Research implications suggest the effectiveness of incorporating local words and ethnic representation in the restaurants’ names to bring in economic benefits and international branding.